Tastes of the divine: Hindu and Christian theologies of emotion - Roberts, Michelle Voss (Comparative theology: thinking across traditions, 2014)
The intensity and meaningfulness of aesthetic experience have often been described in theological terms. By designating basic human emotions as rasa, a word that connotes taste, flavor, or essence, Indian aesthetic theory conceptualizes emotional states as something to be savored. At their core, emotions can be tastes of the divine. In this book, the methods of the emerging discipline of comparative theology enable the author's appreciation of Hindu texts and practices to illuminate her Christian reflections on aesthetics and emotion